Reduction in Carbon Dioxide Emission and Energy Saving Obtained by Renovation of Building Envelope of Existing Residential Buildings - Rui Chen; Xiaoping Feng; Chengjing Li; Huapeng Chen (Aerosol and Air Quality Research)
Abstract Reducing energy consumption and carbon dioxide (CO2) emissions in the construction industry is integral to solving environmental issues, which affect the whole of society and have become increasingly prominent. We selected a residential dwelling from the many buildings in southern Jiangsu Province, China, which consume and emit extremely large amounts of energy and CO2, respectively, and assessed various energy-saving renovation schemes for improving the thermal envelope. First, we used energy consumption simulation software (BESI) to individually analyze the energy performance of each scheme. Then, setting the static payback period as the evaluation index, we applied the orthogonal test method to determine the economic efficiency of different combinations of schemes. Finally, we identified the optimal combination for conserving energy and decreasing CO2 emissions as 120-mm-thick expanded polystyrene insulating board for both the exterior wall and the roof, and 5-mm-thick triple-silver low-emissivity glass and 5-mm-thick normal glass separated by 12 mm of air for the exterior windows, which resulted in a cooling capacity, heating consumption, total building energy consumption, static payback period, and dynamic payback period of 28.37 kWh m−2 a−1, 4.22 kWh m−2 a−1, 32.59 kWh m−2 a−1, 13.76 years, and 22.84 years, respectively, as well as an annual reduction in CO2, sulfur dioxide (SO2), and nitrogen oxides (NOx) emissions of 86.01 tons, 2.59 tons, and 1.29 tons, respectively.